Impact of Wind Driven Variability on Sea Surface Temperature and Ocean Colour in False Bay - Seymour, Sian (Department of Oceanography, 2020)
False Bay is the largest true bay in South Africa and is an important area for conservation, the local fishing industry and marine based recreational activities. A large amount of studies, both recent and historical, have been carried out on the biology of the bay, but studies on the physics of the bay are very few in comparison. In this study high resolution satellite imagery is used to investigate wind variability and its impact on sea surface temperature (SST) and chlorophyll concentration (Chl-a) variability within False Bay and the Cape Peninsula region. High resolution (1 km) coastal winds derived from the Sentinel-1 satellite Synthetic Aperture Radar (SAR) show that winds are strongly influenced by topography under the predominantly south-easterly wind regime. The Hottentots Holland mountain range and Cape Peninsula mountain range create wind shadows as well as areas of increased wind speed within False Bay and west of the Cape Peninsula. Our observations also show that global atmospheric models, such as ECMWF, are not able to capture the spatial variability in the wind fields driven by the orography. Analyses of the SST and ocean colour imagery show that wind shadows are generally associated with warmer surface waters and higher Chl-a. In contrast, regions of enhanced wind speeds show colder surface waters and decreased chlorophyll concentration. Our results suggest that spatial variation in the horizontal wind fields have direct and significant impact on the water properties within False Bay. This study highlights the need for high resolution wind observations and simulations to force regional oceanic models of False Bay and the Cape Peninsula region.